The Construction in Progress of a Private Archive (diségno, 2022)
A few years ago, from an idea born in 2015 on the occasion of a specific study on the professional activity of women architects in Palermo [1], Dacia and Sabina Di Cristina, daughters of the architect and university professor Luciana Natoli (fig. 1), born in 1936 and passed away too early, in 1978, at the age of 42, started to ‘build’ their mother’s archive.Natoli’s young age might suggest a modest size of the archive; in fact, the opposite is absolutely the case.It was in fact the sheer quantity of rolls, files, heliographic copies, drawings on tracing paper and sketch paper, photographs, correspondence, books and magazines that for so many years prevented her daughters from ordering this great mass of content. [read more]